Colonial Legacies in the Repatriation of Cultural Objects: A Content Analysis of Dutch Policies (2020–2024) - Indrarini, Nurul; Yeremia Lalisang, Ardhitya Eduard (Global South Review, 2025)
Amid growing global awareness of historical justice and the rights of formerly colonized nations in the Global South over their cultural heritage, the repatriation of colonial cultural objects has become increasingly prominent in Dutch foreign policy. This article analyzes how official Dutch discourse constructs representations of former colonies in government documents concerning cultural object repatriation between 2020 and 2024. Through qualitative content analysis, applying Herrmann et al.'s (1997) image theory, the study identifies narrative patterns that combine recognition of ownership rights with emphasis on procedures and cooperation mechanisms within Dutch policy frameworks. The findings reveal a discursive shift from colonial-era imagery toward partnership rhetoric, yet paternalistic concerns regarding technical standards, conservation, and governance capabilities persist. This representation frames repatriation as an asymmetrical cultural cooperation rather than mere object return. The study contributes to postcolonial international relations scholarship by demonstrating how repatriation discourse serves as an arena for negotiating meaning, legitimacy, and power relations between former colonial powers and newly sovereign states.